Development of the MapMe intervention body image scales of known weight status for 4–5 and 10–11 year old children. (28th November 2017) - Jones, A R; Tovée, M J; Cutler, L R; Parkinson, K N; Ells, L J; Araujo-Soares, V; Pearce, M S; Mann, K D; Scott, D; Harris, J M; Adamson, A J
Abstract: Background: Parents tend to visually assess children to determine their weight status and typically underestimate child body size. A visual tool may aid parents to more accurately assess child weight status and so support strategies to reduce childhood overweight. Body image scales (BIS) are visual images of people ranging from underweight to overweight but none exist for children based on UK criteria. Our aim was to develop sex- and age-specific BIS for children, based on British growth reference (UK90) criteria. Methods: BIS were developed using 3D surface body scans of children, their associated weight status using UK90 criteria from height and weight measurements, and qualitative work with parents and health professionals. Results: Height, weight and 3D body scans were collected (211: 4–5 years; 177: 10–11 years). Overall, 12 qualitative sessions were held with 37 participants. Four BIS (4–5-year-old girls and boys, 10–11-year-old girls and boys) were developed. Conclusions: This study has created the first sex- and age-specific BIS, based on UK90 criteria. The BIS have potential for use in child overweight prevention and management strategies, and in future research. This study also provides a protocol for the development of further BIS appropriate to other age groups and ethnicities.